Calcium and bone health ‐ goodbye, calcium supplements?. (3rd September 2015) - Ströhle, A.; Hadji, P.; Hahn, A.
Abstract: This review assesses (1) the potential role of calcium supplements in the prevention and treatment of osteoporosis and osteoporotic fractures, and (2) the safety of calcium supplements with respect to cardiovascular health as well. With regard to (1), a total calcium intake of < 800 mg/day is associated with increased loss of bone mineral density in peri- and postmenopausal women with an increase in fracture risk. Hereby, the effect of calcium supplements on fracture prevention is dependent primary on baseline calcium intake. The strongest protective effect has been reported in individuals with a calcium intake < 700 mg/day and in high-risk groups. A calcium intake of about 1000–1200 mg/day seems to be sufficient for general fracture prevention. With regard to (2), an analysis of the data based on the Hill criteria does not demonstrate convincing evidence that calcium supplements increase cardiovascular risk. In the long term, total calcium intake of 2500 mg/day (from food and supplements) continues to be classified as safe. This value should not be exceeded for an extended period of time.